Standard Enucleation with Aluminium Oxide Implant (Bioceramic) Covered with Patient's Sclera. (30th April 2012) - Zigiotti, Gian Luigi; Cavarretta, Sonia; Morara, Mariachiara; Nam, Sang Min; Ranno, Stefano; Pichi, Francesco; Lembo, Andrea; Lupo, Stefano; Nucci, Paolo; Meduri, Alessandro
Abstract : Purpose . We describe in our study a modified standard enucleation, using sclera harvested from the enucleated eye to cover the prosthesis in order to insert a large porous implant and to reduce postoperative complication rates in a phthisis globe. Methods . We perform initially a standard enucleation. The porous implant (Bioceramic) is then covered only partially by the patient's sclera. The implant is inserted in the posterior Tenon's space with the scleral covering looking at front. All patients were followed at least for twelve months (average followup 16 months). Results . We performed nineteen primary procedures (19 patients, 19 eyes, x M;x F) and secondary, to fill the orbital cavity in patients already operated by standard evisceration (7 patients, 7 eyes). There were no cases of implant extrusion. The orbital volume was well reintegrated. Conclusion . Our procedure was safe and effective. All patients had a good cosmetic result after final prosthetic fitting and we also achieved good prothesis mobility.